SPATIAL STRUCTURES OF CLOSED PROFILES (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article presents a new design of steel space trusses, arches, frames of complex application, the main advantages of which are lightness, durability of plane, cost efficiency, reliability, reduction of construction period and investment cycle, energy savings at manufacture, transportation and construction. Based on the previously performed experimental and theoretic studies, the expediency of using box-shaped section parallel chord trusses has been proved. Therefore, new constructive decisions for light efficient trusses, arches, frames that can be used at erection of civil and industrial objects are presented below. The suggested efficient structure of a steel truss with spatial upper chord, using tubes or rectangular hollow box-shaped sections, steel trifurcate spatial truss construction, spatial arch truss, spatial arch. Considered the use of closed cross-sections for spatial arch elements. It has been revealed that using the two-hinges spatial frame the construction cost of a building can be reduced due to reducing of the basement’s dimensions.
Keywords: steel truss; arch; frame; box-shaped section